Core competencies for diabetes educators: a scoping review protocol. (June 2018) - Alharbi, Talal; McIntyre, Meredith; Thomacos, Nikos; McLelland, Gayle
Abstract : Review question/objective: The purpose of the proposed review is, firstly, to map the core competencies for diabetes educators, as reported in the literature, and secondly, to review currently used criteria for core competencies in the assessment of diabetes educators.